Mechanically-sensitive miRNAs bias human mesenchymal stem cell fate via mTOR signalling - Jessica E. Frith (Nature Portfolio, 2018)
Mesenchymal stem cell (MSC) fate can be mechanically regulated by substrate stiffness but this is difficult to control in a 3D hydrogel. Here the authors identify miRNAs that change expression in response to substrate stiffness and RhoA signalling and show that they can bias MSC fate in a 3D soft hydrogel.